ASEAN as 'Compartmentalized Regionalism': A Preliminary Discussion - Choiruzzad, Shofwan Al Banna (Global: Jurnal Politik Internasional, 2017)
This article tries to offer a new ontological perspective to scrutinize ASEAN as a form of 'compartmentalized regionalism'. In contrast to the general view of ASEAN diplomatic practitioners and academics who see the history of ASEAN as an evolution of a regional project that in the political and security dimension becomes a multidimensional regional region through 'widening and deepening', the idea of 'compartmental regionalism' replaces the development of ASEAN as the development of two separate regionalism projects in a single entity. Both regionalism projects have different settings, supplemented by different actors, and work based on differing logic. Thus, the development of ASEAN should not be seen merely as 'widening and deepening', but as the development of two different regionalism projects and the complex interaction between the two.